Cellular and molecular determinants of all‐trans retinoic acid sensitivity in breast cancer: Luminal phenotype and RARα expression. Issue 7 (17th April 2015) - Centritto, Floriana; Paroni, Gabriela; Bolis, Marco; Garattini, Silvio Ken; Kurosaki, Mami; Barzago, Maria Monica; Zanetti, Adriana; Fisher, James Neil; Scott, Mark Francis; Pattini, Linda; Lupi, Monica; Ubezio, Paolo; et al.
Abstract Forty‐two cell lines recapitulating mammary carcinoma heterogeneity were profiled for all‐trans retinoic acid (ATRA) sensitivity. Luminal and ER+ (estrogen‐receptor‐positive) cell lines are generally sensitive to ATRA, while refractoriness/low sensitivity is associated with a Basal phenotype and HER2 positivity. Indeed, only 2 Basal cell lines (MDA‐MB157 and HCC‐1599) are highly sensitive to the retinoid. Sensitivity of HCC‐1599 cells is confirmed in xenotransplanted mice. Short‐term tissue‐slice cultures of surgical samples validate the cell‐line results and support the concept that a high proportion of Luminal/ER+ carcinomas are ATRA sensitive, while triple‐negative (Basal) and HER2‐positive tumors tend to be retinoid resistant. Pathway‐oriented analysis of the constitutive gene‐expression profiles in the cell lines identifies RARα as the member of the retinoid pathway directly associated with a Luminal phenotype, estrogen positivity and ATRA sensitivity. RARα3 is the major transcript in ATRA‐sensitive cells and tumors. Studies in selected cell lines with agonists/antagonists confirm that RARα is the principal mediator of ATRA responsiveness. RARα over‐expression sensitizes retinoid‐resistant MDA‐MB453 cells to ATRA anti‐proliferative action. Conversely, silencing of RARα in retinoid‐sensitive SKBR3 cells abrogates ATRA responsiveness. All this is paralleled by similar effects on ATRA‐dependent inhibition of cell motility, indicating that RARα may mediate also ATRA anti‐metastatic effects. We define gene sets of predictive potential which are associated with ATRA sensitivity in breast cancer cell lines and validate them in short‐term tissue cultures of Luminal/ER+ and triple‐negative tumors. In these last models, we determine the perturbations in the transcriptomic profiles afforded by ATRA. The study provides fundamental information for the development of retinoid‐based therapeutic strategies aimed at the stratified treatment of breast cancer subtypes.